PENCEMARAN AIR OLEH LIMBAH TAHU DI TUKAD BADUNG DENPASAR TERKAIT PENEGAKAN HUKUM LINGKUNGAN OLEH PEMERINTAH PROVINSI BALI - Kadafi, Mu’ammar; Mudana, Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
This research was entitled “Water Contamination by Tofu Waste in Tukad Badung Denpasar Related to Environmental law Enforcement by the Government of Bali Province”, meanwhile the background of this research issue was that the Government of Bali Province had issued the regulation regarding the environment, however in practice the regulation still was felt ineffective particularly water contamination issue by tofu waste in Tukad Badung. Based on the background, the author raised the formulation of the problem among others: How does the existence of the Government of Bali Province on environmental law enforcement and what are the efforts conducted by the Government of Bali Province to overcome the contamination of tofu waste in the area of Tukad Badung, Denpasar. The research was empiric law research, which emphasized more on the law effectiveness, which based on the source of primary law material, secondary law material and tertiary law material, meanwhile to collect the data from the field it utilized the interview and document study. Based on the research discussion, the result was obtained that the Government of Bali Province had issued the Regional Regulation of Bali Province No.4 year 2005 and also the Regulation of Governor of Bali No.8 year 2007 but ineffective, because what it required here is Administrative Environmental Law Enforcement in particular.
Keywords: Government, Water Contamination, Environmental law Enforcement, Existence